Classical Islamic Political Thought: Study of Sunni Perspectives - Suyadi Suyadi; Ahmad Fikri Sabiq (Islah: Journal of Islamic Literature and History, 2020)
The purpose of this study is to determine the Islamic political thought in classical Islam in the perspective of the Sunni sect. This research is a qualitative research which is library research. Data collection method is library data that has been selected, searched, presented and analyzed. This study uses data analysis techniques in the form of content analysis. Content analysis is a scientific analysis of the message content of a data. One of the characteristics of the classical era Islamic political thought is that it does not question the position of religion and state, whether integrated or separate. The debates that occurred in the classical era on the establishment of a state, the election of a head of state, and the conditions that a head of state must-have. Besides, political thought that develops also tends to be a response to the prevailing socio-political conditions. The emergence of Sunni ideology is a form of anxiety over the viewpoints developed by groups that tend to discredit the position of the Prophet's companions who are considered by some on the opposite side to have committed treason or treason. For Sunnis, leadership after the death of the Prophet Muhammad was open and not limited to ahl Bayt. A background that is considered appropriate and competent can be proposed as a leader. Thus, the appointment or appointment of the caliph as the legal ruler depends on the specific qualities possessed by the prospective leader.